Analisis Kendala Peserta Didik dalam Menyelesaikan Soal Operasi Hitung Campuran pada Pembelajaran Matematika - Theresia Varenchi; Dwi Athana Suherman; Adrias Adrias; Salmaini Putri Syam (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This research aims to analyze students' learning difficulties in solving mathematical problems, especially in mixed arithmetic operations at the elementary school level. The method used is Systematic Literature Review (SLR), which collects and analyzes relevant previous research. The research results show that most students have difficulty in understanding questions and doing arithmetic operations, especially in the arithmetic operations section (90% of students have difficulties). Common mistakes include errors in concepts, procedures, and operations, caused by lack of understanding, inaccuracy, and confusion in the order of processing questions. Internal factors such as attitude and motivation as well as external factors such as ineffective teaching methods also affect this difficulty. This research suggests solutions in the form of improving arithmetic exercises, improving the understanding of basic mathematical concepts, using relevant learning media, as well as guidance and remedial for students with difficulties. A creative learning approach is needed to overcome this challenge.